Ocean Acidification Alleviates Dwarf Eelgrass (Zostera noltii) Lipid Landscape Remodeling under Warming Stress - Bernardo Duarte; Tiago Repolho; José Ricardo Paula; Isabel Caçador; Ana Rita Matos; Rui Rosa (Biology, 2022)
Coastal seagrass meadows provide a variety of essential ecological and economic services, including nursery grounds, sediment stabilization, nutrient cycling, coastal protection, and blue carbon sequestration. However, these ecosystems are highly threatened by ongoing climatic change. This study was aimed to understand how the dwarf eelgrass Zostera noltii leaf lipid landscapes are altered under predicted ocean warming (+4 °C) and hypercapnic (ΔpH 0.4) conditions. Warming and hypercapnic conditions were found to induce a severe reduction in the leaf total fatty acid, though the combined treatment substantially alleviated this depletion. The lipid discrimination revealed a significant increase in the relative monogalactosyldiacylglycerol (MGDG) content in both hypercapnic and warming conditions, allied to plastidial membrane stabilization mechanisms. Hypercapnia also promoted enhanced phosphatidylglycerol (PG) leaf contents, a mechanism often associated with thylakoid reinvigoration. In addition to changing the proportion of storage, galacto- and phospholipids, the tested treatments also impacted the FA composition of all lipid classes, with warming exposure leading to decreases in polyunsaturated fatty acids (PUFAs); however, the combination of both stress conditions alleviated this effect. The observed galactolipid and phospholipid PUFA decreases are compatible with a homeoviscous adaptation, allowing for the maintenance of membrane stability by counteracting excessive membrane fluidity. Neutral lipid contents were substantially increased under warming conditions, especially in C18 fatty acids (C18), impairing their use as substrates for fatty acylated derivatives essential for maintaining the osmotic balance of cells. An analysis of the phospholipid and galactolipid fatty acid profiles as a whole revealed a higher degree of discrimination, highlighting the higher impact of warming and the proposed stress alleviation effect induced by increased water-dissolved CO2 availability. Still, it is essential to remember that the pace at which the ocean is warming can overcome the ameliorative capacity induced by higher CO2 availability, leaving seagrasses under severe heat stress beyond their lipid remodeling capacity.